Quality measurement methods for video assisting refereeing systems - Brunnström, K.; Djupsjöbacka, A.; Ozolins, O.; Billingham, J.; Wistel, K.; Evans, N. (Sports Engineering, 2023)
Changes in the footballing world`s approach to technology and innovation, along with major advancements in broadcasting contributed to the decision by the International Football Association Board to introduce Video Assistant Referees in 2018. The change meant that under strict protocols referees could use video replays to review decisions in the event of a "clear and obvious error" or a "serious missed incident". At the time of writing 48-Member Associations have introduced the Video Assistant Referees protocol in at least one of their tournaments and there are many technology providers who work with organisers to implement the Video Assistant Referees systems. To ensure that the use of Video Assistant Referees has a positive effect on the game, Fédération Internationale de Football Association collaborated with the RISE Research Institutes of Sweden to develop objective test methods that could be used to ensure that a system can provide an adequate solution. Each provider must be able to pass requirements that ensure that they can deal with the challenges of processing, coding, decoding, synchronising, and re-formatting of the broadcast feeds. This article will describe the development of the test methods and illustrate some initial results from a test event on Video Assistant Referees system candidates. The methods have shown to be robust and appropriate for their intended purpose and will be developed over the years to ensure the quality of Video Assistant Referees. The developed measurement methods are general and can be applied to other broadcast and video systems as well as to other sports.